Sumatriptan Nasal Spray for Acute Migraine - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
A multicenter, randomized, double-blind, placebo-controlled trial of sumatriptan nasal spray (5 mg, 10 mg, and 20 mg) was conducted in 653 adolescents presenting with acute migraine at the Palm Beach Headache Center, Florida; Cleveland Clinic, OH; Michigan Headache Institute, Ann Arbor; and San Antonio Center, TX.